Urine neutrophil gelatinase-associated lipocalin concentration in healthy newborns during the first three postnatal days - Mikulić, Vinka (Array, 2020)
Introduction: Urine neutrophil gelatinase-associated lipocalin (uNGAL) is a biochemical marker significant for early prediction of acute kidneyinjury in adults. However, it has not been examined sufficiently among the infant population, particularly newborns in terms of reference values.The aim of our study was to determine the concentration of uNGAL in healthy term newborns and to determine if there was a difference in uNGALconcentration according to gender, postnatal age and birth weight.Materials and methods: Our study involved 81 healthy term newborns birth (≥ 37 weeks, Apgar score ≥ 8 in the first minute after birth, CRP <5mg/L). Urine NGAL was measured using chemiluminescent microparticle immunoassay (CMIA) within 72 hours after birth, on Architect plus ci8200analyser (Abbott, Chicago, USA). Data were analysed using Statistica software.Results: The median concentration of uNGAL in the whole study group of healthy term newborns was 27.1 ng/mL (16.5-56.0 ng/mL) (newborn girls,27.1 ng/mL (15.8-47.9 ng/mL); newborn boys, 27.9 ng/mL (16.5-61.0 ng/mL), P = 0.941). Median uNGAL concentration according to postnatal ageexpressed in days was 28.2 ng/mL (11.7-57.2 ng/mL) 1st day, 28.9 ng/mL (16.5-64.2 ng/mL ) 2nd day and 23.9 ng/mL (20.2-46.6) 3rd day, P = 0.863.Regarding birth weight for newborns <3500 g, median concentration was 25.0 ng/mL (16.5-45.4 ng/mL ) and for weight ≥ 3500 g 30.6 ng/mL(16.5-64.2 ng/mL), P = 0.455.Conclusions: There were no significant difference in uNGAL concentration in relation to gender, postnatal age and birth weight.